The Relationship Between Spiritual Conditions and the Quality of Life of the Elderly in UPTD X - Kalasta Ayunda Putri; Diah Retno Wahyuningrum (Professional Evidence-based Research and Advances in Wellness and Treatment, 2025)
Seniors experience various physical, psychological, and social changes that can impact their quality of life. One factor believed to improve their well-being is spirituality. Seniors with high spiritual levels tend to better face life’s challenges, show stronger psychological resilience, and have a higher quality of life. This study aims to examine the relationship between spiritual condition and quality of life among the elderly in UPTD X. An analytical observational design with a cross-sectional approach was used in this study. The sample consisted of 80 elderly individuals selected through Simple Random Sampling from a population of 100. Data were collected using the Daily Spiritual Experience Scale (DSES) questionnaire to measure spiritual condition and the Older People Quality of Life (OPQOL) questionnaire to assess the elderly’s quality of life. Data analysis was conducted using the Spearman Rho Correlation Test due to non-normal distribution. Results show that most seniors have a moderate to high spiritual condition. Those more active in spiritual activities tend to have a better quality of life than those with low spirituality. The correlation test revealed a significant relationship between spiritual condition and quality of life (r = 0.512, p = 0.001), indicating a medium-level correlation. The study concludes that better spiritual conditions lead to higher quality of life. To enhance elderly well-being in social institutions, interventions such as improving religious programs, providing better social support, and training health workers in spiritual guidance are essential.